2020
DOI: 10.3390/antiox9010068
|View full text |Cite
|
Sign up to set email alerts
|

Bardoxolone-Methyl (CDDO-Me) Suppresses Androgen Receptor and Its Splice-Variant AR-V7 and Enhances Efficacy of Enzalutamide in Prostate Cancer Cells

Abstract: Androgen receptor (AR) signaling is fundamental to prostate cancer (PC) progression, and hence, androgen deprivation therapy (ADT) remains a mainstay of treatment. However, augmented AR signaling via both full length AR (AR-FL) and constitutively active AR splice variants, especially AR-V7, is associated with the recurrence of castration resistant prostate cancer (CRPC). Oxidative stress also plays a crucial role in anti-androgen resistance and CRPC outgrowth. We examined whether a triterpenoid antioxidant dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 73 publications
2
21
0
2
Order By: Relevance
“…Quercetin is able to reduce the migration and invasion of human skin melanoma cells SK-MEL-28, increasing the expression of epithelial markers and decreasing mesenchymal markers [32]. The combination of Stevia pilosa and Stevia eupatoria with enzalutamide did not induce an antagonist effect on the migration of cells, which is consistent with wound-healing assay with enzalutamide alone reported by Khurana, et al [33], and different from the antagonist effect reported by the same group with enzalutamide and sulforaphane in resistant cells [34]. Based on the above, we suggest that the extracts could affect some of these mechanisms, however, additional studies are needed.…”
Section: Discussionsupporting
confidence: 89%
“…Quercetin is able to reduce the migration and invasion of human skin melanoma cells SK-MEL-28, increasing the expression of epithelial markers and decreasing mesenchymal markers [32]. The combination of Stevia pilosa and Stevia eupatoria with enzalutamide did not induce an antagonist effect on the migration of cells, which is consistent with wound-healing assay with enzalutamide alone reported by Khurana, et al [33], and different from the antagonist effect reported by the same group with enzalutamide and sulforaphane in resistant cells [34]. Based on the above, we suggest that the extracts could affect some of these mechanisms, however, additional studies are needed.…”
Section: Discussionsupporting
confidence: 89%
“…The remaining compounds either showed a lower level of bioactivity compared to SM (pi-153) or were unable to affect motility of tumor cells at all (TM, pi-156). The obtained results are in line with published data: recently, we found that SM at identical concentration (0.5 µM) effectively inhibited migration of RAW264.7 macrophages [64]; furthermore, SM's structural analog CDDO-Me and its derivatives significantly reduced motility of both malignant [65][66][67][68][69] and non-malignant [70][71][72] cells at submicromolar concentrations (0.05-1 µM). Revealed differences in the level of inhibitory activity of investigated compounds against tumor cell motility are consistent with the level of their cytotoxicity.…”
Section: Discussionsupporting
confidence: 92%
“…ABT263 drug could increase ubiquitin/proteasome-dependent degradation of AR and AR-v7 proteins through the ROS/USP26 axis, enhancing CRPC cell sensitivity to Enzalutamide [ 130 ]. Besides, acute exposure (2 h) to CDDO-Me increased ROS levels to suppresses AR and its splice-variant AR-V7 at both the transcriptional and translational levels [ 131 ].…”
Section: Roles Of Ros Molecules In Pcamentioning
confidence: 99%